Mangifera indica L. kernel ethanol extract inhibits cell viability and proliferation with induction of cell cycle arrest and apoptosis in lung cancer cells - Alshwyeh, Hussah Abdullah; Al-Sheikh, Warqaa Muhammed Shariff; Rasedee, Abdullah; Alnasser, Sulaiman Mohammed; Al-Qubaisi, Mothanna Sadiq; Ibrahim, Wisam Nabeel (Taylor and Francis, 2024)
In this study, we investigated the effects of an ethanolic extract of Mangifera indica L. kernel on the viability and proliferation of human lung cancer cells. We utilized MTT and BrdU cell proliferation assays, morphological assessments, cell cycle analyses, and apoptosis assays to investigate the extract’s effects on lung cancer (A549 and NCI-H292) and normal lung (MRC-5) cells. The extract demonstrated a toxicity toward cancer cells compared to normal cells with dose-dependent anti-proliferative effect on lung cancer cells. The extract also caused differential effects on the cell cycle, inducing G0/G1 arrest and increasing the Sub-G1 population in both lung cancer and normal lung cells. Notably, the extract induced loss of membrane integrity, shrinkage, membrane blebbing, and apoptosis in lung cancer cells, while normal cells exhibited only early apoptosis. Furthermore, the extract exhibited higher toxicity towards NCI-H292 cells, followed by A549 and normal MRC-5 cells in decreasing order of potency. Our results suggest that the ethanolic extract of M. indica L. kernel has significant potential as a novel therapeutic agent for treating lung cancer cells, given its ability to induce apoptosis in cancer cell lines while causing minimal harm to normal cells.